Content Marketing: Using it effectively for Brand Strategy and Customer Relationship Management - Odongo, Ignatius (Advances in Social Sciences Research Journal, 2016)
Content is continuously produced by both companies and the public in form of reviews, comments, and status updates, in avenues such as; websites, social media, product review boards, message boards, blogs, emails, video presentations, slideshows, podcasts, online groups, articles, press releases and testimonials. Unfortunately, this is what makes content marketing a double edged sword – positive or negative – depending on the experiences customers have had with the company and its products and services. If users post positive messages about the company, it shows that the company is doing something right. Conversely, if the messages are negative, they could water down and cause irreparable damage to the company’s reputation and image. Hence, companies need to take these messages seriously because they shape the perceptions of consumers towards brands. This review paper utilises meta-synthesis to explore content marketing, and explain how both the internet and social media have influenced the creation of appropriate content for company products and services. The paper provides valuable lessons and key success factors that can enable companies to develop and utilise both their own content and that generated by customers, to grow their brands and create increased traffic and business to themselves.